THE COGNITIVE AND LINGUISTIC ASPECTS OF VERBS OF MOTION IN ENGLISH - Boboyarova D.F (Scholar Express Journal, 2023)
This scientific article explores the intricate relationship between language, cognition, and the expression of motion events in the English language. Verbs of motion play a crucial role in describing how entities move in space, and their analysis provides valuable insights into the cognitive representations of motion. Drawing on linguistic research, cognitive science, and psycholinguistics, this paper investigates the syntactic and semantic structures of motion verbs, their metaphorical extensions, and the role of gestures in their linguistic expression. Additionally, the article discusses how these linguistic expressions contribute to the construction of spatial conceptualization and communication in English-speaking communities.
Keywords: Verbs of motion; English language; motion events; metaphorical extensions